Domestic Architectural Transformation and Cultural Continuity: The Case of Fala Kanci in Ternate City - Sherly Asriyani; Maulana Ibrahim; Arham Munir (Jurnal Ilmiah Teknik, 2026)
Rapid urbanization in Ternate City has intensified pressure on domestic housing and accelerated changes in traditional dwellings such as Fala Kanci, raising challenges for adaptation without losing cultural identity. Objective: This study investigates how urbanization pressures, socio-economic conditions, and cultural values interact in shaping the spatial, material, and functional transformation of Fala Kanci domestic architecture across different urban contexts in Ternate City. Method: A qualitative approach was applied through field observations, in-depth interviews, questionnaires, and visual documentation of 36 Fala Kanci houses located in interior, peripheral, and urban core zones. Data were examined using thematic and comparative analysis to identify transformation patterns and cross-zone variations. Findings: Transformations occur unevenly. Urban core areas show the most intensive spatial expansion, increased material substitution from organic to industrial components, and broader functional diversification. Peripheral areas display mixed adaptation patterns, while interior areas exhibit stronger intergenerational continuity and greater preservation of traditional forms. Despite extensive physical modification, key cultural values communal interaction, family orientation, and symbolic identity remain embedded in spatial organization and selected architectural elements. Implications: The findings support context-sensitive strategies for architects, planners, and heritage practitioners to balance housing adaptation with cultural continuity in rapidly urbanizing island cities. Originality: This research contributes an integrative household-level account linking urbanization dynamics, socio-economic strategies, and cultural persistence an aspect often underexplored in vernacular architecture and urban studies.